Quantum coherence in a processable vanadyl complex: new tools for the search of molecular spin qubits. Issue 3 (5th January 2016) - Tesi, Lorenzo; Lucaccini, Eva; Cimatti, Irene; Perfetti, Mauro; Mannini, Matteo; Atzori, Matteo; Morra, Elena; Chiesa, Mario; Caneschi, Andrea; Sorace, Lorenzo; Sessoli, Roberta
Abstract : A multitechnique investigation of an evaporable vanadyl spin system with long-lived quantum coherence that self-assembles on gold. Abstract : Electronic spins in different environments are currently investigated as potential qubits, i.e. the logic units of quantum computers. These have to retain memory of their quantum state for a sufficiently long time (phase memory time, T m ) allowing quantum operations to be performed. For molecular based spin qubits, strategies to increase phase coherence by removing nuclear spins are rather well developed, but it is now crucial to address the problem of the rapid increase of the spin–lattice relaxation rate, T 1 −1, with increasing temperature that hampers their use at room-temperature. Herein, thanks to the combination of pulsed EPR spectroscopy and AC susceptometry we evidence that an evaporable vanadyl complex of formula VO(dpm)2, where dpm − is the anion of dipivaloylmethane, presents a combination of very promising features for potential application as molecular spin-qubit. The spin–lattice relaxation time, T 1, studied in detail through AC susceptometry, decreases slowly with increasing temperature and, more surprisingly, it is not accelerated by the application of an external field up to several Teslas. State-of-the art phase memory times for molecular spin systems in protiated environment are detected by pulsed EPR also in moderate dilution, with values of 2.7 μs at 5 K and 2.1 μs at 80 K. Low temperature scanning tunnel microscopy and X-ray photoelectron spectroscopy in situ investigations reveal that intact molecules sublimated in ultra-high vacuum spontaneously form an ordered monolayer on Au(111), opening the perspective of electric access to the quantum memory of ensembles of spin qubits that can be scaled down to the single molecule.